2019
DOI: 10.1371/journal.pone.0211984
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the choice of primary care facilities for initial treatment among rural and urban residents in Southwestern China

Abstract: ObjectiveTo explore influential factors contributing to the choice of primary care facilities (PCFs) for the initial treatment among rural and urban residents in Southwestern China.MethodsA face-to-face survey was conducted on a multistage stratified random sample of 456 rural and 459 urban residents in Sichuan Province from January to August in 2014. A structured questionnaire was used to collect data on residents’ characteristics, provider of initial treatment and principal reason for the choice. Multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 48 publications
3
26
0
Order By: Relevance
“…This user view might be partly linked to the belief that good facilities and equipment of large hospitals guarantee good qualities of care. [13,23] Similar user misperception and distorted health-seeking behaviors were also reported in China; community individuals preferred to seek care in second or tertiary hospitals rather than primary care facilities, although the latter provide more accessible and affordable care. An important driver for this health-seeking behavior was trust in doctors in tertiary hospitals.…”
Section: Primary Care Services Of Community Clinicsmentioning
confidence: 75%
See 2 more Smart Citations
“…This user view might be partly linked to the belief that good facilities and equipment of large hospitals guarantee good qualities of care. [13,23] Similar user misperception and distorted health-seeking behaviors were also reported in China; community individuals preferred to seek care in second or tertiary hospitals rather than primary care facilities, although the latter provide more accessible and affordable care. An important driver for this health-seeking behavior was trust in doctors in tertiary hospitals.…”
Section: Primary Care Services Of Community Clinicsmentioning
confidence: 75%
“…An important driver for this health-seeking behavior was trust in doctors in tertiary hospitals. [13] Therefore, efforts to raise public trust in primary care physicians and facilities are essential.…”
Section: Primary Care Services Of Community Clinicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beijing ecology of care study5, for example, demonstrated fewer number of people seek primary care physicians in the community as their first contact care compared with a similar study conducted in the USA. People prefer tertiary care hospitals in urban centres for their first contact care 6…”
Section: Strengthening Primary Care Through Family Medicinementioning
confidence: 99%
“…To address the gap in medical quality between urban and rural areas, many previous studies found that compared with the healthcare institutions in the rural areas of China, those in the urban areas are equipped with more and better health resources, such as financial, human, and material resources [41]. As a result, the level of patient satisfaction and experience in China's public hospitals seemed to be higher in the urban than in the rural areas [42].…”
Section: Interpretation Of Findingsmentioning
confidence: 99%